A comprehensive study on in situ stress field characteristics and changes in rock mechanical properties in deep mines in northeastern Yunnan, China - Hui Wang; Bangtao Sun; Cong Cao; Shibo Yu; He Wang; Ye Yuan; Hua Zhong (Deep Underground Science and Engineering)
Abstract The Maoping lead–zinc mining area is a significant metal mine site in northeastern Yunnan. In this study, both hydraulic fracturing in situ stress testing and ultrasonic imaging logging were first carried out in the mining area. Second, 930 focal mechanism solutions and 231 sets of stress data near the mining area were collected. Then, the variations in the type of in situ stress field, the magnitude of in situ stress, the direction of horizontal principal stress, and the ratio of lateral pressure were analyzed to characterize the distribution of the in situ stress field. On this basis, a new method using borehole breakouts and drilling‐induced fractures was proposed to determine the stress direction. Finally, the evolution of the mechanical properties of dolomite with burial depth was analyzed and the influence of rock mechanical properties on the distributions of the in situ stress field was explored. The results show that the in situ stress in the mining area is σH > σV > σh, indicating a strike–slip stress state. The in situ stress is high in magnitude, and its value increases with burial depth. The maximum and minimum horizontal lateral stress coefficients are stabilized at approximately 1.22 and 0.73, respectively. The direction of the maximum horizontal principal stress is NW, mainly ranging from N58.44° W to N59.70° W. The stress field inferred from the focal mechanism solution is in good agreement with the test results. The proportion of structural planes with dip angles between 30° and 75° exceeds 80%, and the dip direction of the structural planes is mainly NW to NWW. The line density of structural planes shows high density in shallow areas and low density in deep areas. More energy tends to be accumulated in rocks with higher elastic modulus and strength, leading to higher in situ stress levels. These findings are of significant reference for mine tunnel layout, support design optimization, and disaster prevention.